The 'Bottle Villa' Of Illusions and Desires: A Critical Study of The Tragic Heroines of Atwood's Surfacing and Tenesse William's A Streetcar Named Desire - et. al., Aiswarya Jayan, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
"Obstinately she tried to control and defy her destiny and to know her story is to be inspired by pity and terror" - Elain Dundy The literary landscape resounds with the echoing hollering of the great tragic heroes, whose Homeric lives had made the literary vista resplendent. But amidst the din, there exists the complex caricatures of tragic heroines who stuns us with the sheer intensity of the paroxysm that is their lives. Tennessee Williams and Margaret Atwood has given the world two such heroines whose lives are akin to the constrictor knots i.e their lives tighten and strangles them as they try to escape from it. This paper is a novel attempt to collate the tortuous characters of these women who has intrigued the audience with their fascinating psyches.